Editorial board, information for authors, and other front matter - Joan Thomson (Journal of Applied Communications, 2008)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 92, no. 1-2 (2008) of Journal of Applied Communications
Keywords: masthead